O INCIDENTE PROCESSUAL DE DESCONSIDERAÇÃO DA PERSONALIDADE JURÍDICA: atualização da disregard doctrine na perspectiva da responsabilidade patrimonial e reflexos no processo civil brasileiro - Chamberlain, Hector Cavalcanti (2020)
The present work addresses the disregard of legal personality s incident , a procedure defined as a modality of intervention by third parties in the Civil Procedure Code of 2015, regulated by articles 133 to 137. The incident represents an innovative leg